circ_ZFR Is Linked to Paclitaxel Resistance in Cervical Cancer via miR-944 Sponging and IL-10 Upregulation - Xiaoqian Long; Meiyun Zheng; Youlin Yang; Yi Chen; Xiahui Zhang; Haiyan Zhang (Analytical Cellular Pathology)
Objective. Cervical cancer (CC) has an elevated rate of invasion and death despite surgical treatment, radiotherapy, and chemotherapy. Several studies revealed that circRNAs have a key contribution to the resistance of drugs against different types of carcinomas. The goal of the existing study was to figure out what role circ_ZFR plays in paclitaxel (PTX) resistance in cervical cancer (CC) patients. Materials and Methods. Herein, two types of CC cells (SiHa/PTX and Hela/PTX) were utilized. The levels of IL-10 mRNA, miR-944, and circ_ZFR were measured using qRT-PCR analyses. The CCK-8 assay was used to determine PTX resistance. The IL-10 expression was measured via the ELISA technique. The combination of miR-944 and circ_ZFR or IL-10 was validated using a dual-luciferase reporter (DLR) assay. Results. The amount of circ_ZFR was increased in PTX-resistant CC cells and tissues. In PTX-resistant CC cells, knocking down circ_ZFR expression decreased PTX resistance. circ_ZFR knockdown significantly reduced IL-10 expression via sponging miR-944, increasing PTX sensitivity in PTX-resistant CC cells. Conclusion. circ_ZFR knockdown has a considerable role in overwhelming CC-associated PTX resistance by modifying the axis of miR-944/IL-10 axis, suggesting that developing a circRNA target-based treatment could be considered prevent CC progression.